Care workers, the unacknowledged persons in person-centred care: A secondary qualitative analysis of UK care home staff interviews. - Adam Kadri (PLoS ONE, 2018)
Personhood discourses in dementia care have gained prominence and current care home standards mandate that care should be "person-centred". However, it is unclear how the personhood of staff is construed within the care relationship. This paper aims to explore how the personhood of paid carers of people with dementia can be understood by focussing on the views and experiences of care home staff. We undertook a secondary qualitative analysis of interviews with 25 paid care staff in England, conducted as part of the MARQUE (Managing Agitation and Raising QUality of lifE) study. The authors inductively developed themes around the topic of personhood for staff, contrasting management and care staff perspectives. We found that many care staff are not identified as persons in their own right by their employing institutions, and that there is a general lack of acknowledgment of the moral work of caring that occurs within formal care work. This oversight can reduce the complex relationships of care work to a series of care tasks, challenges care workers' self-worth and self-efficacy, and impede their efforts to deliver person-centred care. We conclude that care staff status as persons in their own right should be explicitly considered in quality standards and supported by employers' policies and practices, not simply for their role in preserving the personhood of people with dementia but for their own sense of valued personhood. Enhancing staff personhood may also result in improved care.